Hacking code/space: Confounding the code of global capitalism - Zook, M; Graham, M (Wiley, 2018)
Information-technologies are essential for global capitalism to function at speed across scale, space and complexity. The importance of software and algorithms in the governance of these systems is reflected in the attention of scholars to the ways digital code and materiality (re)combine to create hybrid digital/material spaces of economic activity, movement and everyday life. This paper extends this work in two key ways: first by emphasising the relational aspect of these code/ spaces, and second by showing how the digital algorithms of code/spaces are hackable rather than hegemonic. Using the case study of frequent flyer programmes we demonstrate how networked knowledge-sharing reshapes code/spaces to provide unintended opportunities such as low-cost travel and access to spaces normally only frequented by global elites. Although this case highlights vulnerabilities in the code of global capitalism, it is primarily only those with significant lifestyle privilege who are able to fully participate in these subversions. Moreover, while much of the value captured by “airline hackers” comes from airlines’ profit margins, the relationality of code/spaces can impact citizens and consumers not directly connected to or interested in airline travel. Ultimately, this paper demonstrates that in contrast to characterisations of omnipresence and hegemony, the information networks and algorithms of global capitalism contain moments of uneven porousness and selective hackability.